Evaluation of appropriateness of prescription and polypharmacy in the geriatric population: a cross sectional study at a comprehensive geriatric clinic in a tertiary care hospital - Chowta, Mukta N.; Adhikari, Prabha M.; Raj, Sheetal; Laxman, Mridula; Kariappa, Ahalya; George, Jincy; Shetty, Meenakshi A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To assess the prescription quality in a comprehensive geriatric clinic and to determine the frequency of inappropriate prescription and polypharmacy. Methods: Both males and female patients above the age of 60 y attending a comprehensive geriatric clinic of a tertiary care hospital were included in the study. Medications taken by the patients, excluding vitamins, minerals and herbal medications were counted in each patient and analyzed by considering their medical history and using universally accepted tools like medication appropriateness index, START, STOPP & Beer's criteria. In this study, polypharmacy was considered as having 6 or more medications per prescription. Results: A total of 120 patients were included in the study. Around 82 (68.33%) patients had less than 6 prescribed medications and 38 patients (31.66%) were on 6 or more than 6 medications. The number of medications used by the patients is 4.37Â±2.33. Around 21 (17.5%) were on medications that are not indicated, 25 patients (20.83%) were receiving medications which are to be avoided in elderly as per the Beer's and STOPP criteria. Medication was underused in 24 patients (20%) as per START criteria. When both overused drugs and drugs to be avoided were considered for assessment of inappropriateness, 39 patients (32.5%) were found to be receiving inappropriate medication. Among the drugs to be avoided in elderly, amitriptyline was the most common drug and was used in 15 (12.5%) patients. Antihypertensives were the most common potential prescribing omissions in geriatric patients. Conclusion: Polypharmacy is seen in a significant proportion of geriatric patients. Inappropriate prescription and potential prescribing omissions were observed in a significant proportion of geriatric patients. Keywords: Polypharmacy, Geriatrics, Beer's criteria, STOPP criteria